Induction of cell cycle arrest and apoptosis in caspase-3 deficient MCF-7 cells by Dillenia suffruticosa root extract via multiple signalling pathways - Foo, Jhi Biau; Saiful Yazan, Latifah; Tor, Yin Sim; Armania, Nurdin; Ismail, Norsharina; Imam, Mustapha Umar; Yeap, Swee Keong; Cheah, Yoke Kqueen; Abdullah, Rasedee; Ismail, Maznah (BioMed Central, 2014)
Background: Dillenia suffruticosa root dichloromethane extract (DCM-DS) has been reported to exhibit strong cytotoxicity towards breast cancer cells. The present study was designed to investigate the cell cycle profile, mode of cell death and signalling pathways of DCM-DS-treated human caspase-3 deficient MCF-7 breast cancer cells. Methods: Dillenia suffruticosa root was extracted by sequential solvent extraction. The anti-proliferative activity of DCM-DS was determined by using MTT assay. The mode of cell death was evaluated by using inverted light microscope and Annexin-V/PI-flow cytometry analysis. Cell cycle analysis and measurement of intracellular reactive oxygen species (ROS) were performed by using flow cytometry. MCF-7 cells were co-treated with antioxidants α-tocopherol and ascorbic acid to evaluate whether the cell death was mainly due to oxidative stress. GeXP-based multiplex system was employed to investigate the expression of apoptotic, growth and survival genes in MCF-7 cells. Western blot analysis was performed to confirm the expression of the genes. Results: DCM-DS was cytotoxic to the MCF-7 cells in a time-and dose-dependent manner. The IC50 values of DCM-DS at 24, 48 and 72 hours were 20.3 ± 2.8, 17.8 ± 1.5 and 15.5 ± 0.5 μg/mL, respectively. Cell cycle analysis revealed that DCM-DS induced G0/G1 and G2/M phase cell cycle arrest in MCF-7 cells at low concentration (12.5 and 25 μg/mL) and high concentration (50 μg/mL), respectively. Although Annexin-V/PI-flow cytometry analysis has confirmed that DCM-DS induced apoptosis in MCF-7 cells, the distinct characteristics of apoptosis such as membrane blebbing, chromatin condensation, nuclear fragmentation and formation of apoptotic bodies were not observed under microscope. DCM-DS induced formation of ROS in MCF-7 cells. Nevertheless, co-treatment with antioxidants did not attenuate the cell death at low concentration of DCM-DS. The pro-apoptotic gene JNK was up-regulated whereby anti-apoptotic genes AKT1 and ERK1/2 were down-regulated in a dose-dependent manner. Western blot analysis has confirmed that DCM-DS significantly up-regulated the expression of pro-apoptotic JNK1, pJNK and down-regulated anti-apoptotic AKT1, ERK1 in MCF-7 cells. Conclusion: DCM-DS induced cell cycle arrest and apoptosis in MCF-7 cells via multiple signalling pathways. It shows the potential of DCM-DS to be developed to target the cancer cells with mutant caspase-3.